Pelatihan Pengembangan Usaha bagi Manajemen Koperasi Pusat Koperasi Unit Desa (PUSKUD) Mataram Provinsi Daerah Istimewa Yogyakarta - Nurhayat Indra (LPPM Universitas Koperasi Indonesia, 2023)
Field work practice activity (PKL) for Indonesian Cooperative University students is a concrete manifestation of community service for students and lecturers. In the even semester of 2023, the activities of student are entirely focused on cooperatives in Daerah Istimewa Yogyakarta Province, one of which is the Mataram Puskud. The form of dedication as the real work of students and lecturers in this cooperative is business development training and the preparation of a cooperative business plan whose participants are representatives of management, supervisors, managers and employees. The training method used is the adult training method (andragogy). The results of the training evaluation indicated that the new training was able to provide competency knowledge and (cognitive) insights for the participants, but it was still not effective in changing the attitudes and skills of the participants in seeking breakthroughs in cooperative business development in a situation of intense market competition.